(untitled) (Progressive Agriculture, 2016)
The present study was conducted in the Soil Science Field Laboratory at Bangladesh Agricultural University, Mymensingh during November 2014 to April 2015 to study the effect of moringa leaf extract on growth and yield of maize. The experiment comprised of five treatments viz., T1 (control), T2 (water sprayed at every 2 weeks, starting from 2 weeks after emergence), T3 (moringa leaf extract sprayed at 2 weeks after emergence), T4 (moringa leaf extract sprayed at 2 and 4 weeks after emergence) and T5 (moringa leaf extract sprayed at 2 weeks after emergence and at every 2 weeks thereafter). The experiment was laid out in a Randomized Complete Block Design (RCBD) with 3 replications. Application of moringa leaf extract at 2 weeks after emergence and at every 2 weeks thereafter (T5) significantly increased growth parameters like plant height, shoot length, fresh weight and dry weight of shoot, and yield components like number of grains cob-1, 100-grain weight, grain weight plant-1. The highest grain yield (9.2 t ha-1), stover yield (10.1 t ha-1) and harvest index (48%) were obtained from T5 while the lowest grain yield (6.3 t ha-1), stover yield (8.6 t ha-1) and harvest index (42%) were found in the treatments where no moringa leaf extract was used (T1 or T2). From the results it can be concluded that moringa leaf extract should be applied for better growth and yield performance of maize in Old Brahmaputra Floodplain soil of Bangladesh. Progressive Agriculture 27 (2): 136-143, 2016